Responsibility and laboratory animal research governance - McLeod, Carmen; Hartley, Sarah (Sage, 2017)
The use of animals in experiments and research remains highly contentious. Laboratory animal research governance provides guidance and regulatory frameworks to oversee the use and welfare of laboratory animals and relies heavily on the replacement, reduction, and refinement (3Rs) principles to demonstrate responsibility. However, the application of the 3Rs is criticized for being too narrow in focus and closing down societal concerns and political questions about the purpose of animal laboratory research. These critiques challenge the legitimacy of responsibility in laboratory animal research governance and call for new approaches. With the advent of the "Responsible Research and Innovation" (RRI) agenda, we investigate whether the notion of responsibility in the controversial area of animal research governance could be enhanced by examining the 3Rs through RRI. Our analysis reveals RRI has the potential to helpfully augment the 3Rs in three key ways: recognizing the need to include a broader range of experts and publics in animal research governance; emphasizing the importance for animal research scientists of taking societal, and not just role, responsibilities into account; and acknowledging the political questions animal research raises.